Structural analysis of a submerged cylindrical shell subjected to two consecutive spherical shock waves. (January 2018) - Iakovlev, S.
Abstract: Three-dimensional structural dynamics of a circular cylindrical shell submerged in fluid and subjected to two consecutive spherical shock waves is addressed using a semi-analytical model based on the classical apparatus of mathematical physics. It is established that for certain values of the delay between the first and second incident wavefronts, the highest stress observed in the system significantly (by up to 50%) exceeds the peak stress observed for the single-front loading of the same intensity. Although this result is quantitatively the same as the one reported for the simplified two-dimensional model of the system, it is demonstrated that there exist very substantial differences between the evolution of the peak stress predicted by the two models when the three-dimensionality of the incident shock waves is pronounced. It is thus established that the presented three-dimensional model is a far more reliable pre-design analysis tool for such loadings than its two-dimensional counterpart.